Plasmonic rK28 ELISA improves the diagnosis of canine Leishmania infection - Oliveira dos Santos Maciel, Marilene [UNESP]; Soares, Matheus Fujimura [UNESP]; Costa, Sidnei Ferro [UNESP]; Bragato, Jaqueline Poleto [UNESP]; Rebech, Gabriela Torres [UNESP]; de Freitas, Jéssica Henrique [UNESP]; Alves, Graziella Borges [UNESP]; de Oliveira, Talita Carolina Bragança [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Wiley, 2020)
In this study, we evaluated the performance of a new enzyme-linked immunosorbent assay (ELISA) variant known as indirect “plasmonic ELISA” (pELISA) for the detection of Leishmania spp. infection. Serum samples from 170 dogs from an area where canine leishmaniosis (CanL) is endemic and from 26 healthy dogs from a nonendemic area were tested by indirect pELISA, and the results were compared to those of an indirect ELISA (both with recombinant antigen rK28) and those of an immunochromatographic test (dual-path platform, TR-DPP®) using real-time PCR on blood samples or conjunctival swabs as the gold standard. The pELISA, indirect rK28 ELISA and the TR-DPP® immunochromatographic test presented sensitivities of 94.7%, 89.5% and 79.0% and specificities of 100%, 92.7% and 91.5%, respectively. The analysis of the results revealed that the specificity of the indirect pELISA was greater than that of the method recommended by the Ministry of Health in Brazil and may increase the feasibility of diagnosis in resource-constrained countries because it does not require sophisticated instruments to read. Thus, this method can be used as an additional tool for the detection of Leishmania spp. infection in these areas.
Keywords: diagnosis; dogs; enzyme-linked immunosorbent assay; metal nanoparticles; visceral leishmaniosis